2011
DOI: 10.1073/pnas.1018501108
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α promotes fracture repair by augmenting the recruitment and differentiation of muscle-derived stromal cells

Abstract: With an aging population, skeletal fractures are increasing in incidence, including the typical closed and the less common open fractures in normal bone, as well as fragility fractures in patients with osteoporosis. For the older age group, there is an urgent unmet need to induce predictable bone formation as well as improve implant fixation in situations such as hip joint replacement. Using a murine model of slow-healing fractures, we have previously shown that coverage of the fracture with muscle accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
299
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(312 citation statements)
references
References 52 publications
10
299
2
1
Order By: Relevance
“…The simplicity of this model compared with a closed or open fracture model (eg, smaller and more confined callus formation, lack of gait defect) supports a direct role for muscle/bone crosstalk in fracture healing [12,19,21,28]. Previous studies using closed and open fracture models have reported conflicting findings over the potential benefit (or lack thereof) of muscle paralysis on fracture healing [3,13].…”
Section: Discussionmentioning
confidence: 73%
“…The simplicity of this model compared with a closed or open fracture model (eg, smaller and more confined callus formation, lack of gait defect) supports a direct role for muscle/bone crosstalk in fracture healing [12,19,21,28]. Previous studies using closed and open fracture models have reported conflicting findings over the potential benefit (or lack thereof) of muscle paralysis on fracture healing [3,13].…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, this study demonstrated that GDNF cooperated with the cytokine TNF-α to stimulate osteoblastic cell growth suggesting an interaction between GDNF and TNF-α signalling pathways in osteoblasts. TNF-α has been ascribed a multifunctional role in bone metabolism (22); TNF-α effects may involve a proresorptive (osteoclastic bone degradation) action during inflammatory conditions (21), but TNF-α has also been recognised as an anabolic cytokine stimulating osteogenic migration, proliferation and differentiation (46)(47)(48)(49)(50). Interestingly, TNF-α has been shown to have neuroprotective capabilities which in part may be dependent on induction of cytoprotective neutrotrophic growth factors such as GDNF (51-53).…”
Section: Discussionmentioning
confidence: 99%
“…Altered endochondral callus formation has been reported as a result of manipulation of macrophages and or macrophage-expressed molecules, but the experimental designs did not specifically target these molecules during the anabolic phase. 28,29,34,45 Therefore, altered inflammatory progression/resolution cannot be ruled out as a contributing mechanism to the observed compromised fracture repair. Carefully timed manipulation of macrophages and/or their products is required to elucidate the pro-anabolic contributions of macrophages to bone repair via endochondral ossification.…”
Section: Macrophage Contributions To Early Anabolism During Fracturementioning
confidence: 99%
“…Experimentally, elevated systemic inflammation due to additional soft-tissue trauma injuries impairs fracture healing, 42,43 confirming that persistence of a proinflammatory environment is one mechanism responsible for detrimental fracture healing. 44 Interestingly, low-dose TNF administered to the fracture site at the time of surgery and 1 day post surgery improved fracture healing in mice, 45 suggesting that TNF, and potentially macrophage activation, has complex dose-and time-dependent outcomes on bone healing.…”
Section: Macrophage Contributions To Inflammation During Fracture Repairmentioning
confidence: 99%